Resistance Wrapped in Prayer: Spirituality and Religiosity in the Kamang War in Minangkabau - Prawira, Danang Agung; Nopriyasman; Putri, Selfi Mahat (Universitas Islam Negeri Raden Intan Lampung, 2026)
The Kamang War was part of the Belasting War of 1908. This resistance is regarded as one of the regional wars that significantly influenced the struggle of the Minangkabau people. This article explores how spirituality and religiosity were present and became essential elements in the Kamang War. This study employed the historical method using a qualitative approach to systematically reconstruct and analyze past events based on historical sources obtained through library research and interviews with members of the Kamang community. The interviews were conducted to explore the community's collective memory of the spirituality and religiosity associated with the Kamang War. The findings reveal that spirituality essentially a connection with the transcendent served as both a driving force behind the outbreak of the war and as an instrument shaping its course. Through mystical ritual practices imbued with symbolic meaning, spirituality functioned as a strategic tool for traditional societies in warfare. These rituals acted as mechanisms for attack, defense, motivation, social solidarity, and the reaffirmation of collective belief in the legitimacy of their struggle. As tensions escalated, scholars of the Syattariyah Sufi Order (Tarekat Syattariyah) played a pivotal role in instilling resistance among the populace against Dutch colonial policies. Religious conviction inspired the Minangkabau people to fight for a sacred mission, as the war against the Dutch was perceived as a form of jihad.